Do music festival communities address environmental sustainability and how? A Scottish case study. Issue 2 (May 2019) - Brennan, Matt; Scott, Jo Collinson; Connelly, Angela; Lawrence, Gemma
Abstract: This article discusses the findings of an Arts and Humanities Research Council project researching how music festival communities in Scotland can address issues of environmental sustainability and climate change. It investigates how music festival communities are constructed with a focus on what role, if any, they might play in responding to the global challenge of environmental sustainability. Using music festivals in Scotland as a case study, we employed a variety of research methods to interrogate different constituents in music festival communities about their views and behaviours regarding climate change and environmental sustainability. These included festival audiences via onsite questionnaires; festival organisers and promoters via interviews and focus groups; and musicians via creative practice-led research. We conclude that rather than necessarily being a site for progressive or utopian socio-cultural experimentation (as they are occasionally portrayed in festival literature), music festival communities engage in complex and often contradictory behaviours when it comes to responding to – and making sense of – their own complicity in social challenges such as climate change.